Security Testing Using Intrusion Detection System in Cloud Computing - Augustin Anggeliung; Arief Dwi Rachmadian; Vincent Vincent (Bina Nusantara University, 2020)
The development of technology is very fast, one of them is cloud computing. Cloud computing has been used from various circles and began to be developed. There are various problems that arise in cloud computing, such as problems from data, whether the data will be safe. To ensure that the data is safe, several methods or tools can be used. In this scientific work we use the Intrusion Detection System as an aid tool needed to access the network, including whether packages can protect data in cloud computing. Although the intrusion detection system there are still some shortcomings such as only being able to read some data and the performance will decrease the data very much. To overcome this it is necessary to use several additional tools such as the Intrusion Prevention System which is a refinement of the Intrusion Detection System and using the AES algorithm